Physiotherapists’ Perspectives on the Role of Physiotherapy in Medical Tourism in India - Chandramohan , R.; Prabhusanker , C. N.; Sedhunivas , R.; Nikhilesh , D. Arnold (Recent Advances in Commerce, Management, and Tourism, 2023)
Role of tourism in the economic growth of any country is evident. Medical tourism is one of the important segments in the tourism industry for country like India. Indian tourism industry has witnessed the rise in medical tourism in recent past. Medical tourism studies have focused on types of surgery, management, and guest facility but least attention has been given to the role of healthcare professionals. There is an ambiguity on to what extant various categories of healthcare professionals can play their role. Therefore, the current study focuses on exploring the awareness and role of physiotherapists in medical tourism in India. Using exploratory research design and convenient data collection method, it has collected 213 samples from physiotherapists across the India. The results indicate that most of the physiotherapists are not aware of medical tourism practices and very few are associated with any hospitals for such services. It also provides the managerial implications for the hospital mangers.